1982
DOI: 10.1128/iai.38.3.817-824.1982
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of migration of human monocytes by bacterial cell walls and muramyl peptides

Abstract: Bacterial cell walls, water-soluble fragments of the wall peptidoglycan, Nacetylmuramyl-L-alanyl-D-isoglutamine (MDP), and 6-0-acyl derivatives of MDP were examined for migration-stimulating activity on human peripheral blood monocytes by using a multiwell chemotaxis assembly. Cell walls isolated from 11 bacterial species caused a definite increase in monocyte migration, but the walls of Micrococcus lysodeikticus were scarcely active. The migration-enhancing activity of Staphylococcus epidermidis cell walls wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The assay for enhanced migration of monocytes by test materials was performed with a multiwell chemotaxis assembly (Neuro Probe, Cabin John, Md.) as described previously (24). The number of monocytes that migrated to the surface of the membrane sheet adjacent to the lower well containing an added test specimen was determined in triplicate for each experimental point.…”
Section: Methodsmentioning
confidence: 99%
“…The assay for enhanced migration of monocytes by test materials was performed with a multiwell chemotaxis assembly (Neuro Probe, Cabin John, Md.) as described previously (24). The number of monocytes that migrated to the surface of the membrane sheet adjacent to the lower well containing an added test specimen was determined in triplicate for each experimental point.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these synthetic peptide segments are considered to be in addition to the infiammatory peptides derived from bacterial components. We previously demonstrated that //-acetylmuramyl-L-alanyl-D-isoglutamine (MDP), the minimum effective structure responsible for the majority of multifold immunomodulating activities of bacterial cell wall peptidoglycans, also enhanced chemotactic activity of human monocytes in a wide range of doses from 0.001 -1 /.igl ml (2x10-^-2x10"^ M) under the same experimental conditions (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…A^-formyl-methionyl-leucyl-phenylalanine (FMLP) was purchased from Sigma Chemical Co., St. Louis, MO and dis-solved in ethanol at a concentration of 10"^ M. This preparation was stored at -2O''C in 0.5-ml portions. Each portion was thawed before use, diluted to indicated concentrations with the culture medium described below and used as a positive chemoattractant for chemotaxis assays (9).…”
Section: Chemotactic Agentsmentioning
confidence: 99%
See 2 more Smart Citations